2017
DOI: 10.1136/vetreccr-2017-000538
|View full text |Cite
|
Sign up to set email alerts
|

Progressive neurological deficits after general anaesthesia in a horse

Abstract: An otherwise healthy eight-year-old Irish Sports Horse mare weighing 590 kg underwent general anaesthesia for bilateral tarsal arthroscopy and arthrotomy with subsequent removal of two osseous intra-articular fragments. The horse was positioned in dorsal recumbency, with the pelvic limbs stretched backwards. The anaesthetic was uneventful except for a brief period of hypertension and mild hypoxaemia. However, a bilateral pelvic limb paralysis became evident during recovery, while the thoracic limb function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 18 publications
(28 reference statements)
0
26
0
1
Order By: Relevance
“…5 Dorsal recumbency is also a common feature in horses with suspected spinal cord pathology or bilateral neuropathy. [8][9][10][11][12][13] Subclinical hypovitaminosis E and selenium deficiency may also be implicated. 5 Measurement of vitamin E levels could be considered on an individual basis in horses that may be predisposed to myelopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Dorsal recumbency is also a common feature in horses with suspected spinal cord pathology or bilateral neuropathy. [8][9][10][11][12][13] Subclinical hypovitaminosis E and selenium deficiency may also be implicated. 5 Measurement of vitamin E levels could be considered on an individual basis in horses that may be predisposed to myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Myelopathy following general anaesthesia in the horse has been documented in case reports and series. 5,[7][8][9][10][11][12][13] The underlying pathology is ischaemic damage to the spinal cord and its blood vessels. There is a tendency for 'large-framed' breeds to be affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date only 32 cases of spinal cord myelopathy have been reported. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] It is a poorly understood central neurological condition demonstrated by the variety of names and has been referred to by spinal cord myelomalacia, 17 22 postanaesthetic poliomyelomalacia, 10 postanaesthetic haemorrhagic myelopathy, 23 haematomyelia, 14 spinal cord malacia 9 and postanaesthetic myelopathy. 19 20 Table 1 presents the signalment of previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have looked at factors affecting recovery quality and found that shorter duration of anaesthesia, lower American Society of Anesthesiologists status, less invasive surgery, longer recovery times, lower body mass and younger age were all associated with better quality recovery 11 14. Other commonly encountered morbidities or causes of mortality in the recovery period include postanaesthetic myopathy, neuropathies, respiratory obstruction,10 pulmonary oedema15 and spinal cord malacia 16. Postanaesthetic myopathy was considered as a possibility in this case, however the horse was not distressed, did not exhibit signs of pain and the muscles were not palpably swollen, hard or hot, which are signs typically seen with postanaesthetic myopathy,17 therefore it was effectively ruled out as a possibility.…”
Section: Discussionmentioning
confidence: 99%